Studi Kasus Produk Makanan : Halal atau Haram? : (Studi pada Permen Gelatin dan Makanan Impor) - Nurmayani Nurmayani; Reza Nur Wahyuni; Khayla Andira Salsabila; Saida Adilla; Yuni Sonia (Jurnal Budi Pekerti Agama Islam, 2025)
The certainty of halal status in food products is a crucial issue among Muslim consumers. Products containing additives such as gelatin or those imported from abroad often raise concerns, mainly due to limited information regarding their ingredient composition and production processes. This study aims to investigate the halal status of gelatin-based candy products and various imported foods available in Indonesia. The research employs a descriptive qualitative approach through literature review, product label analysis, and interviews with Islamic jurisprudence experts and representatives from the Halal Product Assurance Organizing Agency (BPJPH). The findings indicate that most gelatin-based candies in the market contain animal-derived gelatin with unclear sources (either bovine or porcine), while many imported products are not yet halal-certified. In conclusion, Muslim consumers should be more selective in choosing food products, and halal certification bodies play a vital role in educating the public and ensuring transparency in halal information.